The Effect of ASN Core Values BerAKHLAK on Employee Performance at the Solok Regency Education Office - Wireziyan Fadhilla; Sinta Westika Putri (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Employee performance is a fundamental determinant of organizational effectiveness in achieving institutional goals. At the Solok Regency Education Office, several performance-related problems remain evident, including delays in task completion, limited employee independence, inadequate competencies due to the absence of structured training programs, and discrepancies between performance appraisal data and field realities. This study aims to examine the effect of the ASN BerAKHLAK Core Values on employee performance at the Solok Regency Education Office. The study employed a quantitative method with a causal associative approach. The research population comprised all Civil Servants (Pegawai Negeri Sipil [PNS]) at the Solok Regency Education Office, totaling 35 individuals, all of whom were selected as the sample through a total sampling technique. Data were collected through questionnaires and analyzed using simple linear regression. The findings indicate that the ASN BerAKHLAK Core Values have a positive and significant effect on employee performance, as shown by a significance value of 0.027 (< 0.05) and a regression coefficient of 0.260. The ASN BerAKHLAK Core Values account for 14% of the variance in employee performance (R Square = 0.140), while the remaining 86% is influenced by other factors not examined in this study. The study concludes that strengthening the internalization of ASN BerAKHLAK Core Values through consistent organizational culture programs and leadership reinforcement is essential for improving employee performance in a broader and more sustainable manner. These findings contribute to the understanding of values-based performance improvement in public sector institutions and offer practical implications for strengthening human resource management within government offices.